Preparation method and application of lightweight bending-resistant nylon 12 composite material
By preparing lightweight resistant nylon 12 composite materials, using aramid pulp, TPEE resin, modified chopped carbon fiber and crosslinking agent, multiple problems in the processing and application of thermoplastic carbon plates for shoes are solved, and the high-efficiency mechanical properties, bending resistance and economic applicability of the material are achieved.
Patent Information
- Application Number
- CN202411762090.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
AI Technical Summary
When preparing thermoplastic carbon plates for shoes, the prior art has problems such as the feeding material and carbon plates that are prone to breaking or whitening during bending, poor water absorption and dimensional stability, and high content of carbon fibers, resulting in high manufacturing costs.
Using a lightweight resistant nylon 12 composite material, a composite material with good mechanical properties and bending resistance is formed by mixing aramid pulp with TPEE resin and intensive extrusion and granulation, combining modified chopped carbon fibers and crosslinking agents.
The composite material has achieved good mechanical properties, lightweight effect, bending resistance, low water absorption rate and good dimensional stability, so that the product does not break or turn white after 20,000 bends, and the manufacturing cost is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation method and application of a lightweight, anti-bending nylon 12 composite material. Background Art
[0002] Thermoplastic carbon plate, with its significant advantages of high strength and recyclability, has quickly become the preferred material in the field of modern sports shoes. It not only provides solid support for sports shoes, but also perfectly integrates dynamic flexibility, accurately adapts to every subtle change of the athlete's footsteps, and ensures the ultimate comfort and safety during exercise. At the same time, its environmental protection characteristics are also in line with modern people's pursuit of sustainable development, leading a new trend in sports shoe materials.
[0003] Polyamide 12 (PA12) is a common engineering plastic with good plasticity, wear resistance and impact toughness. It is often used as a substrate and composited with carbon fiber to make carbon plates for shoes. However, there are the following problems in the actual preparation and application process: First, during the processing, high-content carbon fiber filling is prone to cause material overflow, affecting the processing and preparation process; second, during the blending process of carbon fiber and PA12, the high filling and inert interface easily cause the carbon plate to break or turn white during the bending process; third, thermoplastic carbon plates for shoes require low water absorption (water absorption ≤ 0.5%) and good dimensional stability (shrinkage ≤ 0.5%). PA12 is a crystalline polymer with an amide structure, and the water absorption and dimensional stability of the material are poor, making it difficult to meet application requirements; fourth, to achieve good mechanical properties, it is necessary to fill with high-content carbon fiber (≥ 30%). This practice will significantly increase the manufacturing cost and is not conducive to the promotion and use of products.
[0004] Therefore, developing a lightweight and anti-bending nylon 12 composite material has important economic value and practical significance for improving the use effect and application scope of thermoplastic carbon plates for shoes. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a lightweight anti-bending nylon 12 composite material with good lightweight effect, anti-bending ability and mechanical properties.
[0006] Another object of the present invention is to provide an application of a lightweight, anti-bending nylon 12 composite material.
[0007] In order to achieve the above object, the solution of the present invention is: A method for preparing a lightweight, anti-bending nylon 12 composite material comprises the following steps: Step 1: Break up the aramid pulp, then add N-butylbenzenesulfonamide, and continue stirring for 5-10 minutes to obtain a uniform aramid pulp dispersion. Then mix the aramid pulp dispersion with TPEE resin and melt-extrude and granulate it through a mixer-extruder at an extrusion temperature of 150-220°C to obtain a TPEE-aramid pulp composite. Step 2: Soak the 1-3 cm long chopped carbon fiber in anhydrous ethanol for 0.5-2 hours, then wash and dry with deionized water, put it in a 1.5-3 g / L dopamine hydrochloride solution and stir it at room temperature for 2-4 hours, then add a surface modifier and stir it at 40-70 ° C for 2-4 hours, wash and dry it with deionized water to obtain modified chopped carbon fiber; Step 3: 50 wt%~65 wt% PA12 resin, 20 wt%~35 wt% TPEE-aramid pulp composite, 7wt%~12 wt% modified chopped carbon fiber, 1 wt%~2 wt% cross-linking agent, 0.2 wt%~1 wt% antioxidant and 0.2 wt%~1wt% white oil are melt-extruded and granulated through a twin-screw extruder at an extrusion temperature of 160~230°C to obtain a lightweight, anti-bending nylon 12 composite material.
[0008] Furthermore, in step 1, the mass ratio of the N-butylbenzenesulfonamide to the aramid pulp is 0.03-0.07:1.
[0009] Furthermore, in step 1, the mass ratio of the aramid pulp dispersion to the TPEE resin is 2-3:1.
[0010] Furthermore, in step 2, the mass ratio of the chopped carbon fiber to the dopamine hydrochloride solution is 0.4-0.6:1.
[0011] Furthermore, in step 2, the surface modifier is ethylene glycol diglycidyl ether and / or 1,4-butanediol diglycidyl ether.
[0012] Furthermore, in step 2, the mass ratio of the surface modifier to the dopamine hydrochloride solution is 0.01-0.03:1.
[0013] Furthermore, in step 2, the pH value of the dopamine hydrochloride solution is 8.5.
[0014] Furthermore, in step 3, the cross-linking agent is at least one of epoxy chain extender ADR4468, terminal epoxy silicone oil and styrene-methyl methacrylate-glycidyl methacrylate KL-E4370.
[0015] Furthermore, in step 3, the antioxidant is at least one of antioxidant 1010, antioxidant 1076 and antioxidant 168.
[0016] A lightweight anti-bending nylon 12 composite material is prepared by the preparation method and is used for making thermoplastic carbon plates for shoes.
[0017] After adopting the above technical scheme, the preparation method of a lightweight anti-bending nylon 12 composite material of the present invention has the following advantages: (1) Good mechanical properties and lightweight effect. The use of TPEE-aramid pulp composites, modified short-cut carbon fibers and cross-linking agents to modify PA12 not only achieves multiple improvements in the strength, modulus and toughness of the composite material (tensile strength is not less than 98MPa, basically maintained at 98~105MPa; elastic modulus is not less than 6947MPa, basically maintained at 6947~7532MPa; notched impact strength is not less than 17.6kJ·m 2 , basically maintained at 17.6~20.2kJ·m 2 ), and also reduced the density of the composite material, showing a good lightweight effect (density is not higher than 1.12g / cm 3 , basically maintained at 1.07~1.12g / cm 3 ).
[0018] (2) Good bending resistance. The surface of the modified chopped carbon fiber has reactive groups, which can achieve good composite with PA12, which is conducive to stress transfer; at the same time, the TPEE-aramid pulp in the system has good elasticity and modulus, which can enhance the material's bending resistance; in addition, the introduction of a cross-linking agent can improve the interface between the TPEE-aramid pulp composite, the modified chopped carbon fiber and the matrix resin PA12. The combined effect gives the composite material good bending resistance, so that the product will not break or turn white after 20,000 bends.
[0019] (3) Low water absorption and good dimensional stability. On the one hand, TPEE-aramid pulp and modified short-cut carbon fiber not only have good hydrophobicity, but also have excellent thermal stability, which can maintain or improve the water absorption and dimensional stability of the composite material; on the other hand, by introducing a cross-linking agent to form a certain cross-linking reaction with PA12 resin, the original linear structure can be changed, the steric hindrance can be increased, and the moisture absorption and mobility of the polyamide molecular chain can be inhibited, the water content and internal stress concentration can be reduced, and finally a low water absorption and good dimensional stability can be achieved (the water absorption is not higher than 0.5%, basically maintained at 0.2~0.5%; the shrinkage is not higher than 0.5%, basically maintained at 0.3~0.5%).
[0020] (4) Excellent processing capability and good economic applicability. By introducing components such as TPEE-aramid pulp composite, the carbon fiber filling content is significantly reduced, effectively solving the strong obstruction of carbon fiber during extrusion, which not only gives the composite material excellent processing capability, but also shows good economic applicability. DETAILED DESCRIPTION
[0021] In order to further explain the technical solution of the present invention, the present invention is described in detail below through specific embodiments.
[0022] 1. Material preparation Example 1 A method for preparing a lightweight, anti-bending nylon 12 composite material comprises the following steps: Step 1: The aramid pulp is broken up in a high-speed mixer, and then N-butylbenzenesulfonamide (the mass ratio of N-butylbenzenesulfonamide to aramid pulp is 0.05:1) is added, and stirring is continued for 5 minutes to obtain an aramid pulp dispersion with a uniform appearance, and then the aramid pulp dispersion is mixed with TPEE resin (the mass ratio of aramid pulp dispersion to TPEE resin is 2:1) and melt-extruded and granulated through a mixer extruder at extrusion temperatures of 150°C, 174°C, 216°C, 220°C, 217°C, and 216°C to obtain a TPEE-modified aramid pulp composite; Step 2: Soak 2 cm long chopped carbon fibers in anhydrous ethanol for 0.5 hours, then wash and dry with deionized water, put into 2 g / L dopamine hydrochloride solution (pH = 8.5, mass ratio of chopped carbon fibers to dopamine hydrochloride solution 0.4:1) and stir at room temperature for 2 hours, then add 1,4-butanediol diglycidyl ether (mass ratio of 1,4-butanediol diglycidyl ether to dopamine hydrochloride solution 0.03:1) and stir at 45 ° C for 4 hours, wash with deionized water and dry to obtain modified chopped carbon fibers; Step 3: 50 wt% PA12 resin, 35 wt% TPEE-aramid pulp composite, 12 wt% modified chopped carbon fiber, 1 wt% ADR4468, 1 wt% antioxidant 1076 and 1 wt% white oil are melt-extruded and granulated through a twin-screw extruder at extrusion temperatures of 160°C, 195°C, 228°C, 230°C, 225°C and 225°C to obtain a lightweight, anti-bending nylon 12 composite material.
[0023] Example 2 A method for preparing a lightweight, anti-bending nylon 12 composite material comprises the following steps: Step 1: The aramid pulp is broken up in a high-speed mixer, and then N-butylbenzenesulfonamide (the mass ratio of N-butylbenzenesulfonamide to aramid pulp is 0.07:1) is added, and stirring is continued for 10 minutes to obtain an aramid pulp dispersion with a uniform appearance, and then the aramid pulp dispersion is mixed with TPEE resin (the mass ratio of aramid pulp dispersion to TPEE resin is 3:1) and melt-extruded and granulated through a mixer extruder at extrusion temperatures of 150°C, 177°C, 218°C, 220°C, 216°C, and 215°C to obtain a TPEE-modified aramid pulp composite; Step 2: Soak 3 cm long chopped carbon fibers in anhydrous ethanol for 2 hours, then wash and dry with deionized water, put into 3 g / L dopamine hydrochloride solution (pH = 8.5, mass ratio of chopped carbon fibers to dopamine hydrochloride solution 0.6:1) and stir at room temperature for 4 hours, then add ethylene glycol diglycidyl ether (mass ratio of ethylene glycol diglycidyl ether to dopamine hydrochloride solution 0.01:1) and stir at 65 ° C for 3 hours, wash with deionized water and dry to obtain modified chopped carbon fibers; Step 3: 65 wt% PA12 resin, 24 wt% TPEE-aramid pulp composite, 8 wt% modified chopped carbon fiber, 2 wt% terminal epoxy silicone oil, 0.5 wt% antioxidant 1010 and 0.5 wt% white oil are melt-extruded and granulated through a twin-screw extruder at extrusion temperatures of 160°C, 198°C, 226°C, 230°C, 228°C and 226°C to obtain a lightweight, anti-bending nylon 12 composite material.
[0024] Example 3 A method for preparing a lightweight, anti-bending nylon 12 composite material comprises the following steps: Step 1: The aramid pulp is broken up in a high-speed mixer, and then N-butylbenzenesulfonamide (the mass ratio of N-butylbenzenesulfonamide to aramid pulp is 0.03:1) is added, and stirring is continued for 8 minutes to obtain an aramid pulp dispersion with a uniform appearance, and then the aramid pulp dispersion is mixed with TPEE resin (the mass ratio of aramid pulp dispersion to TPEE resin is 2.6:1) and melt-extruded and granulated through a banburying extruder at extrusion temperatures of 150°C, 182°C, 220°C, 217°C, 217°C, and 215°C to obtain a TPEE-modified aramid pulp composite; Step 2: Soak 1 cm long chopped carbon fiber in anhydrous ethanol for 1.5 hours, then wash and dry with deionized water, put it into 1.5 g / L dopamine hydrochloride solution (pH = 8.5, mass ratio of chopped carbon fiber to dopamine hydrochloride solution 0.55:1) and stir it at room temperature for 3 hours, then add ethylene glycol diglycidyl ether (mass ratio of ethylene glycol diglycidyl ether to dopamine hydrochloride solution 0.016:1) and stir it at 50 ° C for 2 hours, wash with deionized water and dry it to obtain modified chopped carbon fiber; Step 3: 56 wt% PA12 resin, 32 wt% TPEE-aramid pulp composite, 10 wt% modified chopped carbon fiber, 1.2 wt% KL-E4370, 0.3 wt% antioxidant 168, and 0.5 wt% white oil are melt-extruded and granulated through a twin-screw extruder at extrusion temperatures of 160°C, 203°C, 228°C, 230°C, 226°C, and 225°C to obtain a lightweight, anti-bending nylon 12 composite material.
[0025] Comparative Example 1 In this comparative example, PA12, antioxidant 1076 and white oil are directly melt-extruded and granulated through a twin-screw extruder at extrusion temperatures of 160°C, 195°C, 228°C, 230°C, 225°C and 225°C to obtain PA12 material.
[0026] Comparative Example 2 The difference from Example 1 is that, without adding TPEE-aramid pulp composite, the components of this comparative example are 85 wt% PA12 resin, 12 wt% modified chopped carbon fiber, 1 wt% ADR4468, 1 wt% antioxidant 1076 and 1 wt% white oil, and other operations remain unchanged. The extrusion temperatures are 160°C, 195°C, 228°C, 230°C, 225°C, and 225°C to obtain PA12 composite materials.
[0027] Comparative Example 3 The difference from Example 1 is that, in this comparative example, without adding modified chopped carbon fiber, the components are 62wt% PA12 resin, 35wt% TPEE-modified aramid pulp composite, 1wt% ADR4468, 1wt% antioxidant 1076, and 1wt% white oil, and other operations remain unchanged. The extrusion temperatures are 160°C, 195°C, 228°C, 230°C, 225°C, and 225°C to obtain a PA12 composite material.
[0028] Comparative Example 4 The difference from Example 1 is that, in this comparative example, without adding a cross-linking agent, the components are 51 wt% PA12 resin, 35 wt% TPEE-aramid pulp composite, 12 wt% modified short-cut carbon fiber, 1 wt% antioxidant 1076, and 1 wt% white oil; other operations remain unchanged, and the extrusion temperatures are 160°C, 195°C, 228°C, 230°C, 225°C, and 225°C to obtain a PA12 composite material.
[0029] Comparative Example 5 The difference from Example 1 is that, in this comparative example, the chopped carbon fiber is not processed through step 2, and the components are 50 wt% PA12 resin, 35 wt% TPEE-aramid pulp composite, 12 wt% chopped carbon fiber, 1 wt% ADR4468, 1 wt% antioxidant 1076, and 1 wt% white oil. Other operations remain unchanged, and the extrusion temperatures are 160°C, 195°C, 228°C, 230°C, 225°C, and 225°C to obtain a PA12 composite material.
[0030] Comparative Example 6 The difference from Example 1 is that, in this comparative example, TPEE-aramid pulp composite is not added (to increase the content of modified chopped carbon fiber), the components are 62 wt% PA12 resin, 35 wt% modified chopped carbon fiber, 1 wt% ADR4468, 1wt% antioxidant 1076, 1 wt% white oil, and other operations remain unchanged. The extrusion temperatures are 160°C, 195°C, 228°C, 230°C, 225°C, and 225°C to obtain PA12 composite materials.
[0031] Comparative Example 7 The difference from Example 1 is that, in this comparative example, the aramid pulp is not treated with N-butylbenzenesulfonamide, but is directly compounded with TPEE, and the components are 50 wt% PA12 resin, 35 wt% TPEE-aramid pulp composite, 12 wt% modified short carbon fiber, 1 wt% ADR4468, 1 wt% antioxidant 1076 and 1 wt% white oil. Other operations remain unchanged, and the extrusion temperatures are 160°C, 195°C, 228°C, 230°C, 225°C, and 225°C to obtain a PA12 composite material.
[0032] Comparative Example 8 The difference from Example 1 is that in this comparative example, the mass ratio of N-butylbenzenesulfonamide to aramid pulp is 0.02:1, other operations remain unchanged, and the extrusion temperatures are 160°C, 195°C, 228°C, 230°C, 225°C, and 225°C to obtain a PA12 composite material.
[0033] 2. Performance Test The nylon 12 composite materials prepared in each embodiment and comparative example were made into test specimens according to the following relevant performance standards, and the density (GB / T 533), tensile strength (ISO 527-1 / 2), elastic modulus (ISO178 / 2010), notched impact strength (ISO 180 / 2001), bending resistance (GB / T 3903.1-2017), water absorption (GB / T1034-2008) and shrinkage (GB / T 17037.4-2003) of the nylon 12 composite materials were measured. At the same time, the material bubbling during the processing was observed. The results are shown in Table 1.
[0034] Table 1 Nylon 12 composite material performance test data
[0035] It can be seen from the data in Table 1 that the lightweight anti-bending nylon 12 composite materials prepared in Examples 1 to 3 have excellent performance, and the density of the material is not higher than 1.12 g / cm 3 , basically maintained at 1.07~1.12g / cm 3 ; Tensile strength is not less than 98MPa, basically maintained at 98~105MPa; Elastic modulus is not less than 6947MPa, basically maintained at 6947~7532MPa; Notched impact strength is not less than 17.6kJ·m 2 , basically maintained at 17.6~20.2kJ·m 2 The water absorption rate is not higher than 0.5%, and basically maintained at 0.2~0.5%; the shrinkage rate is not higher than 0.5%, and basically maintained at 0.3~0.5%; the product did not break or turn white in the 20,000 bending tests, and the material can be cut normally during the processing without any overflow.
[0036] It can be found from Comparative Example 1 that nylon 12 material has the disadvantages of low strength, high water absorption, large shrinkage and poor bending resistance, making it difficult to use as thermoplastic carbon plate for shoes. By modifying the nylon 12 material, the above disadvantages are effectively overcome, as shown in Examples 1 to 3 in Table 1. Compared with Example 1, in Comparative Example 2, without the addition of TPEE-modified aramid pulp composite, the mechanical strength of the material decreased significantly, the water absorption and shrinkage of the material increased significantly, and the bending resistance of the material deteriorated; in Comparative Example 3, without the addition of modified chopped carbon fiber, the mechanical strength of the material decreased significantly, and the water absorption and shrinkage of the material increased significantly; in Comparative Example 4, without the addition of a cross-linking agent, the mechanical strength of the material decreased slightly, the bending resistance of the material deteriorated, and the water absorption and shrinkage of the material increased slightly; in Comparative Example 5, without the treatment of step 2, the mechanical strength of the material of the chopped carbon fiber decreased to a certain extent. The material's bending resistance deteriorates, and the material's water absorption and shrinkage increase. In Example 6, without adding TPEE-modified aramid pulp composite, the proportion of modified chopped carbon fiber is increased, the material's density increases, and the material's bending resistance deteriorates. In Example 7, when the aramid pulp is not treated with N-butylbenzenesulfonamide, the mechanical strength of the material decreases, the material's bending resistance deteriorates, and the material's water absorption and shrinkage increase. In Example 8, when a low content of N-butylbenzenesulfonamide is added, the material's strength decreases, the material's bending resistance deteriorates, and the material's shrinkage increases, which fails to meet the application requirements.
[0037] After adopting the above technical scheme, the preparation method of a lightweight anti-bending nylon 12 composite material of the present invention has the following advantages: (1) Good mechanical properties and lightweight effect. The use of TPEE-aramid pulp composites, modified short-cut carbon fibers and cross-linking agents to modify PA12 not only achieves multiple improvements in the strength, modulus and toughness of the composite material (tensile strength is not less than 98MPa, basically maintained at 98~105MPa; elastic modulus is not less than 6947MPa, basically maintained at 6947~7532MPa; notched impact strength is not less than 17.6kJ·m 2 , basically maintained at 17.6~20.2kJ·m 2 ), and also reduced the density of the composite material, showing a good lightweight effect (density is not higher than 1.12g / cm 3 , basically maintained at 1.07~1.12g / cm 3 ).
[0038] (2) Good bending resistance. The surface of the modified chopped carbon fiber has reactive groups, which can achieve good composite with PA12, which is conducive to stress transfer; at the same time, the TPEE-aramid pulp in the system has good elasticity and modulus, which can enhance the material's bending resistance; in addition, the introduction of a cross-linking agent can improve the interface between the TPEE-aramid pulp composite, the modified chopped carbon fiber and the matrix resin PA12. The combined effect gives the composite material good bending resistance, so that the product will not break or turn white after 20,000 bends.
[0039] (3) Low water absorption and good dimensional stability. On the one hand, TPEE-aramid pulp and modified short-cut carbon fiber not only have good hydrophobicity, but also have excellent thermal stability, which can maintain or improve the water absorption and dimensional stability of the composite material; on the other hand, by introducing a cross-linking agent to form a certain cross-linking reaction with PA12 resin, the original linear structure can be changed, the steric hindrance can be increased, and the moisture absorption and mobility of the polyamide molecular chain can be inhibited, the water content and internal stress concentration can be reduced, and finally a low water absorption and good dimensional stability can be achieved (the water absorption is not higher than 0.5%, basically maintained at 0.2~0.5%; the shrinkage is not higher than 0.5%, basically maintained at 0.3~0.5%).
[0040] (4) Excellent processing capability and good economic applicability. By introducing components such as TPEE-aramid pulp composite, the carbon fiber filling content is significantly reduced, effectively solving the strong obstruction of carbon fiber during extrusion, which not only gives the composite material excellent processing capability, but also shows good economic applicability.
[0041] In view of the fact that the specially prepared lightweight anti-bending nylon 12 composite material of the present invention has the above-mentioned excellent properties, it is particularly suitable for the production of thermoplastic carbon plates for shoes.
[0042] The above embodiments do not limit the preparation method of the present invention, and any appropriate changes or modifications made thereto by ordinary technicians in the relevant technical field should be deemed to be within the patent scope of the present invention.
Claims
1. A method for preparing a lightweight anti-bending nylon 12 composite material, characterized in that: The following steps are involved: Step 1: Break up the aramid pulp, then add N-butylbenzenesulfonamide, and continue stirring for 5-10 minutes to obtain a uniform aramid pulp dispersion. Then mix the aramid pulp dispersion with TPEE resin and melt-extrude and granulate it through a mixer-extruder at an extrusion temperature of 150-220°C to obtain a TPEE-aramid pulp composite. Step 2: Soak the 1-3 cm long chopped carbon fiber in anhydrous ethanol for 0.5-2 hours, then wash and dry with deionized water, put it in a 1.5-3 g / L dopamine hydrochloride solution and stir it at room temperature for 2-4 hours, then add a surface modifier and stir it at 40-70 ° C for 2-4 hours, wash and dry it with deionized water to obtain modified chopped carbon fiber; Step 3: 50 wt%~65 wt% PA12 resin, 20 wt%~35 wt% TPEE-aramid pulp composite, 7 wt%~12wt% modified chopped carbon fiber, 1 wt%~2 wt% cross-linking agent, 0.2 wt%~1 wt% antioxidant and 0.2 wt%~1 wt% white oil are melt-extruded and granulated through a twin-screw extruder at an extrusion temperature of 160~230°C to obtain a lightweight, anti-bending nylon 12 composite material.
2. The method for preparing a lightweight anti-bending nylon 12 composite material according to claim 1, characterized in that: In step 1, the mass ratio of the N-butylbenzenesulfonamide to the aramid pulp is 0.03-0.07:
1.
3. The method for preparing a lightweight anti-bending nylon 12 composite material according to claim 1, characterized in that: In step 1, the mass ratio of the aramid pulp dispersion to the TPEE resin is 2-3:
1.
4. The method for preparing a lightweight anti-bending nylon 12 composite material according to claim 1, characterized in that: In step 2, the mass ratio of the chopped carbon fiber to the dopamine hydrochloride solution is 0.4-0.6:
1.
5. The method for preparing a lightweight anti-bending nylon 12 composite material according to claim 1, characterized in that: In step 2, the surface modifier is ethylene glycol diglycidyl ether and / or 1,4-butanediol diglycidyl ether.
6. The method for preparing a lightweight anti-bending nylon 12 composite material according to claim 1, characterized in that: In step 2, the mass ratio of the surface modifier to the dopamine hydrochloride solution is 0.01-0.03:
1.
7. The method for preparing a lightweight anti-bending nylon 12 composite material according to claim 1, characterized in that: In step 2, the pH value of the dopamine hydrochloride solution is 8.
5.
8. The method for preparing a lightweight anti-bending nylon 12 composite material according to claim 1, characterized in that: In step 3, the cross-linking agent is at least one of epoxy chain extender ADR4468, terminal epoxy silicone oil and styrene-methyl methacrylate-glycidyl methacrylate KL-E4370.
9. The method for preparing a lightweight anti-bending nylon 12 composite material according to claim 1, characterized in that: In step 3, the antioxidant is at least one of antioxidant 1010, antioxidant 1076 and antioxidant 168.
10. A lightweight, anti-bending nylon 12 composite material, characterized in that: The lightweight, anti-bending nylon 12 composite material is prepared by the preparation method described in any one of claims 1 to 9, and the lightweight, anti-bending nylon 12 composite material is used in the production of thermoplastic carbon plates for shoes.